2012
DOI: 10.3109/10826084.2011.608959
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Peer Group Self-Identification and Adolescent Tobacco Use

Abstract: Associations between peer group self-identification and smoking were examined among 2,698 ethnically diverse middle school students in Los Angeles who self-identified with groups such as Rockers, Skaters, and Gamers. The sample was 47.1% male, 54.7% Latino, 25.4% Asian, 10.8% White, 9.1% Other ethnicity, and 59.3% children of immigrant parents. Multiple group self-identification was common: 84% identified with two or more groups and 65% identified with three or more groups. Logistic regression analyses indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
(19 reference statements)
1
15
0
Order By: Relevance
“…Previous research has demonstrated a difference in smoking rates between peer groups among youth and young adults. 25,26 In Los Angeles, California, researchers determined that the middle school peer group with the highest smoking rates was “Gangsters/Cholos,” who had seven times the odds of smoking. 26 In Richmond, Virginia, among three African American youth and young adult peer crowds, (hip-hop, preppy, and mainstream), the hip-hop peer crowd had increased odds of smoking (AOR=1.97, 95% CI=1.03, 3.76).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated a difference in smoking rates between peer groups among youth and young adults. 25,26 In Los Angeles, California, researchers determined that the middle school peer group with the highest smoking rates was “Gangsters/Cholos,” who had seven times the odds of smoking. 26 In Richmond, Virginia, among three African American youth and young adult peer crowds, (hip-hop, preppy, and mainstream), the hip-hop peer crowd had increased odds of smoking (AOR=1.97, 95% CI=1.03, 3.76).…”
Section: Discussionmentioning
confidence: 99%
“…The peer group associations of youth who label themselves Cholo and Raza may endorse and promote norms more permissive to substance use as well as provide the settings in which to participate in these behaviors. As discussed earlier, studies involving cholo youth suggest that cholos embrace an oppositional culture (Matute-Bianchi, 1986) and even when quite young (i.e., 7th grade) are more likely to smoke cigarettes (Fuqua et al, 2012). The processes through which Cholo and Raza youth come to associate with peer groups who embrace an oppositional culture and the mechanisms and pathways through which those peer groups adopt oppositional values and norms, including permissive views towards substance use, warrant further investigation.…”
Section: Discussionmentioning
confidence: 95%
“…Although some of these labels are derogatory, members of marginalized groups often reclaim and use these labels as an act of resistance. The ethnic labels that people select to describe themselves may provide important information about their ethnic identity, values, relationship with the culture of origin and with the host culture (Bettie, 2000; Fuqua et al, 2012; Matute-Bianchi, 1986), just as the noncultural labels adopted by many adolescents (e.g. jock, brain, popular) express their interests, values, and social norms (Sussman, Pokhrel, Ashmore, & Brown, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, adolescents who identify with crowds such as “Skaters,” “Hip-hop,” and “Hipsters” are more likely to smoke than their peers who identify with crowds such as “Smart Kids” (Fuqua et al, 2012; Lee, Jordan, Djakaria, & Ling, 2013; Ling & Jordan, 2011; Ling et al, 2014; Sussman, Pokhrel, Ashmore, & Brown, 2007). It is not surprising that an increasing number of antismoking campaigns have adopted approaches that target specific peer crowds 1 (for a review see Moran & Sussman, 2014a).…”
mentioning
confidence: 99%